Clinical Practice Guidelines in Colombia - Pío Iván Gómez-Sánchez; Hernando Gaitán Duarte (Federación Colombiana de Obstetricia y Ginecología, 2013)
In this issue we continue with the publication of the Clinical Practice Guidelines (CPG) for the Colombian General Social Security System in Health. The version published in this Journal follows the medical journal format in accordance with the applicable international standards (1). Both the full as well as the abridged versions were published recently by the Ministry of Health and Social Protection (2). Clinical Practice Guidelines (CPG) are defined as a set of recommendations developed systematically to help professionals and patients in their decisionmaking regarding a more appropriate healthcare system, and in selecting the more adequate diagnostic and therapeutic options, when it comes to approach a health problem or a specific clinical condition (3). CPGs were first introduced between the 1950s and the 1970s and gained significant momentum starting in the 1980s, culminating with the mandate from the Agency for Health Care Research and Quality (AHRQ) requiring the development of clinical guidelines in the USA (4). They have become a proposal for health systems in terms of quality improvement, reduction of variations in medical care, and improved organized and efficient management of resources (5, 6). They also come from the medical community, in an attempt to preserve autonomy in an increasingly restrictive environment created by the pressure imposed by the paying and regulatory agencies (7). Over the past few years, many countries have gained considerable experience in the development, assessment and implementation of clinical practice guidelines in professional, institutional, regional and national realms, recognizing that guidelines are a key for improving the quality and relevance of health services (8-10). The consensus required to prepare the guidelines was made possible by the advent of new techniques such as the Delphi methodology (11) the wider use of controlled clinical trials, which gradually became the gold standard for assessing the therapies (12) and methodologies that serve as foundations for evidence-based medicine, such as the definition of answerable questions, systematic searches, and critical approach to the quality of medical literature (13).